Effects of the physisorption properties of human hair-derived activated carbon as a potential electrode for symmetric supercapacitor - Rashed A. M. Adam; Delvina J. Tarimo; Vusani M. Maphiri; Abdulmajid A. Mirghni; Oladepo Fasakin; Ncholu Manyala (Materials for Renewable and Sustainable Energy)
Abstract Herein, human hair-derived activated carbon (HH-AC) with remarkable physisorption properties such as high surface area and well-balanced micro- and mesopores, is synthesized by chemical activation method using potassium hydroxide (KOH). The activated carbon is synthesized at different ratio of charred human hair and activator as 1:1, 1:2 and 1:3 for HH AC(11), HH-AC(12) and HH-AC(13), respectively. These activated materials are characterized by a powder X-ray diffraction (XRD), Laser Raman spectroscopy, Scanning electron microscope (SEM), and $$\:{\text{N}}_{2}$$ adsorption/desorption isotherms. To examine the influence of the micro-mesopore ratio with high surface area on supercapacitor behavior, all samples are tested in a three-electrode using 2.5 moles of potassium nitrate (2.5 M KNO3) as electrolyte solution. The results show that HH-AC(12) sample which has micro to mesopore-balanced $$\:(50:50)\:$$ exhibited superior electrochemical performance with specific capacitance of $$\:215\:\text{F}\:{\text{g}}^{-1}$$ and $$\:125.8\:\text{F}\:{\text{g}}^{-1}$$ in the negative and positive potential, respectively at $$\:1\:\text{A}\:\:{\text{g}}^{-1}$$ . The sample HH-AC(11), which is dominated by micropores, showed lower rate capability and specific capacitance despite the huge surface area.Whereas the HH-AC(13) sample with mostly mesopores achieved higher rate capability compared to the others. The HH-AC(12) is further examined in a 2-electrode setup to form a symmetric device. The results show a specific energy of $$\:16\:\text{W}\text{h}\:\text{k}{\text{g}}^{-1}$$ and a specific power of $$\:375\:\text{W}\:\text{k}{\text{g}}^{-1}$$ at $$\:0.5\:\text{A}\:{\text{g}}^{-1}$$ . The device demonstrates outstanding capacitance retention of $$\:97\text{%}$$ after 10,000 cycles. Thus, ACs with micro to mesopores-balanced are potential candidates for supercapacitor applications.